2021
DOI: 10.1016/j.ejvs.2021.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Editor's Choice – Pre-Operative Moderate to Severe Chronic Kidney Disease is Associated with Worse Short-Term and Mid-Term Outcomes in Patients Undergoing Fenestrated-Branched Endovascular Aortic Repair

Abstract: WHAT THIS PAPER ADDS Analysis of 202 consecutive patients treated with fenestrated-branched endovascular repair (F-BEVAR) for pararenal and thoraco-abdominal aortic aneurysms showed that, despite similarly low peri-operative mortality, subjects with a history of moderate to severe chronic kidney disease (CKD) have higher rates of acute kidney injury than those with unimpaired renal function. Prior CKD was independently associated with renal function decline and poorer survival at midterm follow up. Presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Indeed, the pooled rate of perioperative morbidity is comparatively low in light of some of the contemporary series of surgical conversion after EVAR, [18][19][20] as well as recent series of complex endovascular repair for native aortic aneurysms. 21,22 This supports the adoption of F-BEVAR as the first-line treatment for rescue of postinfrarenal AAA repair failures, provided the anatomy is suitable, although open surgical conversion may still be needed in selected circumstances including cases of graft infection as suggested by contemporary experts opinion and clinical practice guidelines. 23,24 The similar rates of technical success and 5-year survival rates between study groups in the present report would suggest an analogous undertaking, but there are differences that deserve further consideration.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Indeed, the pooled rate of perioperative morbidity is comparatively low in light of some of the contemporary series of surgical conversion after EVAR, [18][19][20] as well as recent series of complex endovascular repair for native aortic aneurysms. 21,22 This supports the adoption of F-BEVAR as the first-line treatment for rescue of postinfrarenal AAA repair failures, provided the anatomy is suitable, although open surgical conversion may still be needed in selected circumstances including cases of graft infection as suggested by contemporary experts opinion and clinical practice guidelines. 23,24 The similar rates of technical success and 5-year survival rates between study groups in the present report would suggest an analogous undertaking, but there are differences that deserve further consideration.…”
Section: Discussionmentioning
confidence: 69%
“…In that sense, the presented cohort is the largest of its kind to date, and the inclusion of an almost equal number of pEVAR and pOAR patients offers important insights in future treatment considerations. Indeed, the pooled rate of perioperative morbidity is comparatively low in light of some of the contemporary series of surgical conversion after EVAR, 18–20 as well as recent series of complex endovascular repair for native aortic aneurysms 21,22 . This supports the adoption of F-BEVAR as the first-line treatment for rescue of postinfrarenal AAA repair failures, provided the anatomy is suitable, although open surgical conversion may still be needed in selected circumstances including cases of graft infection as suggested by contemporary experts opinion and clinical practice guidelines 23,24 …”
Section: Discussionmentioning
confidence: 91%
“…Patients suffering from severe impairment of renal function (GFR<30 ml/min) showed significantly higher rates of all-cause mortality compared with patients with preserved kidney function. The relationship between increased mortality and severity of renal impairment is widely established and has been proven in several studies [Grundmann 2021;Blumenfeld 2022;D'Oria 2021]. The link between renal impairment and survival also underlines the importance of reducing the amount of potentially nephrotoxic contrast agent applications by e.g., avoiding less relevant CTA examinations.…”
Section: E444mentioning
confidence: 96%
“…The revascularization of the renal and visceral arteries during complex aortic surgery entails arterial reconstruction and periods of inherent ischemia until the repair is completed; this can contribute to a variety of complications, whose severity may range from mild to life or organ threatening events with fatal consequences [ 81 ]. Prior studies have shown that the overall incidence of ischemic complications may be intrinsically higher in F/BEVAR procedures as compared with standard EVAR, owing to the higher complexity of such procedures [ 82 ]. The incidence of acute kidney injury (AKI) has been shown to be higher for patients with pre-existing chronic kidney disease (CKD), as defined by eGFR <60 mL/min/1.73 m 2 , compared to those patients with unimpaired renal function (12% vs. 37%, p < 0.001).…”
Section: Acute Kidney Injury and Other Ischemic Complications (Eg Isc...mentioning
confidence: 99%